Home environment predictors of vegetable and fruit intakes among Australian children aged 18 months. (1st August 2019) - Lacy, Kathleen E.; Spence, Alison C.; McNaughton, Sarah A.; Crawford, David A.; Wyse, Rebecca J.; Wolfenden, Luke; Campbell, Karen J.
Abstract: Suboptimal vegetable and fruit consumption by young children is common. Identifying predictors of vegetable and fruit intakes is important for informing strategies to promote sufficient intakes of these foods from early life. The aim of the present study was to examine predictors of toddlers' vegetable and fruit intakes at age 18 months. This study involved secondary analysis of data from 361 child-mother dyads participating in the Melbourne Infant Feeding, Activity and Nutrition Trial in 2008–2010 at child ages four, nine and 18 months. Children's vegetable and fruit intakes were assessed at age 18 months using multiple 24-h dietary recalls. Data on potential predictor measures were collected via parent-completed questionnaires when children were four or nine months of age. Bivariate and multivariable linear regression models were used to test associations between children's average daily vegetable or fruit intake and potential predictors controlling for treatment arm and clustering by parent group. Multivariable models also controlled for covariates and potential confounders. Home availability of vegetables at age nine months was found to predict children's vegetable intake at age 18 months and remained significant (β = 20.19, 95% CI:7.23, 33.15, p = 0.003) in the multivariable model. Children's average daily fruit intake at age 18 months was predicted by maternal education at child age four months and the availability of fruits in their home at child age nine months. Maternal education remained significant (β = 30.83, 95% CI:12.17, 49.48, p = 0.002) in the multivariable model. Strategies to promote adequate vegetable and fruit intakes among young children should address known barriers to the availability of vegetables and fruits in the home from early in life. Additionally, messages encouraging fruit consumption may need to be tailored to mothers with lower levels of education.